Role of FNAC in the Diagnosis of Thyroid Mailgnancy and its Comparison with Histopathology - KC, S; Karki, R; Rayamajhi, P; Rai, K; Piya, E (Nepalese Journal of ENT Head and Neck Surgery, 2013)
Nepalese Journal of ENT Head and Neck Surgery, Vol. 3 Issue 1 (Jan-June 2012) Page 9-10 DOI: http://dx.doi.org/10.3126/njenthns.v3i1.8180